THE CHALLENGES OF GLOBALISATION: EXISTENCE AND EFFORTS IN MAINTAINING CULTURAL IDENTITY - Saptaning Ruju Paminto; Mia Amalia; Ira Permatasari; Salsa Octaviani Suryanto (Fakultas Hukum, Universitas Semarang, 2025)
Culture and social life are one particle that becomes a binding unity, culture faithfully escorts the development of human civilization from pre-Islamic times to the perfect Islamic era as a teaching from ancient Greece to modern times like today. From this long process, culture basically has values that can traditionally be passed on to the next generations. Indonesia is a country that has a lot of culture, which consists of a collection of cultures that exist throughout the Indonesian homeland in the form of local culture. Foreign cultures continue to enter unstoppably into Indonesia which can erode or dilute the local culture owned by the Indonesian people. This problem lies in the need for the government's role in protecting Indonesian culture in the era of globalisation, such as in preserving local culture, the government must facilitate all forms of artistic activities held by the community, besides that the government also has a role to provide support in activities related to culture and open as much as possible the participation of young people or adolescents in maintaining its preservation. The research method used is descriptive method, the foundation of the research method is the philosophy of postpositivism. It aims to be able to determine whether the social and cultural life movement will succeed in having a broad impact and provide changes in living standards as expected.